Neutrophil Recruitment: From Model Systems to Tissue-Specific Patterns. Issue 7 (July 2019) - Margraf, Andreas; Ley, Klaus; Zarbock, Alexander
Abstract : Neutrophil recruitment is not only vital for host defense, but also relevant in pathological inflammatory reactions, such as sepsis. Model systems have been established to examine different steps of the leukocyte recruitment cascade in vivo and in vitro under inflammatory conditions. Recently, tissue-specific recruitment patterns have come into focus, requiring modification of formerly generalized assumptions. Here, we summarize existing models of neutrophil recruitment and highlight recent discoveries in organ-specific recruitment patterns. New techniques show that previously stated assumptions of integrin activation and tissue invasion may need revision. Similarly, neutrophil recruitment to specific organs can rely on different organ properties, adhesion molecules, and chemokines. To advance our understanding of neutrophil recruitment, organ-specific intravital microscopy methods are needed. Highlights: Integrin activation for neutrophil extravasation into inflamed tissue is crucial only in certain tissues, because integrin independent recruitment can occur. Neutrophil integrins can exist in a bent-open headpiece conformation, which can hinder adhesion. Chemotactic cues guide neutrophils for extravasation, including differential chemokine CXCL1/CXCL2 gradients. Activation of the chemokine receptors CXCR2 and CXCR4 can impact neutrophil mobilization and clearance within bone marrow, similarly to mobilization of neutrophils from the marginated pool in the mouse lung. Neutrophils are 'communicative' cells, interacting with other cell populations to exert different functions that can depend on the tissue and/or stimulus.